A problemática entre o particular e o universal: considerações acerca do auditório na argumentação - Radi, Alan Ribeiro (2019)
The figure of the audience assumes great relevance for rhetoric because it plays an active role in making decisions in the argumentative field. Traditionally, this instance is classified as universal and particular. However, the factors that guide this division are not clearly defined by the literature of this field of knowledge, which causes the difficulty of understanding this important argumentative instance. It is necessary to emphasize the understanding of audience underwent some mutations throughout the history. Among the factors that triggered these changes is the reach that the speeches have attained in terms of the media and information technologies in our time. Given the importance of the audience in the persuasive process and the theoretical gap regarding this concept, we aim, in this dissertation, to carry out a theoretical-analytical reflection that allows us to understand the audience instance with greater depth and clarity. Our investigation has retained more attention in the criteria and justifications that guide the subdivision of the audience in particular and universal. We intend, therefore, to clarify obscure points that prevent the fruitful understanding of this concept as well as the studies related to it. In this work, the main authors of the Aristotelian foundation, who directly spoke about the concept of audience, help us to undertake our theoretical reflections, such as: Aristotle (2011), Perelman and Olbrechts-Tyteca (2005), Reboul (2004). Besides those, Tringali (1998), Meyer (2007), Ferreira (2010), Abreu (2001) and Alves (2015) help us undertake our theoretical reflections. We have also count on the studies of Saussure (2001) and Benveniste (1989) regarding linguistic theory and enunciation. To support the theoretical reflections, we analyzed a corpus that sought to unveil the behavior of different speakers and audience through homosexual and gay discourses. This corpus consists of six texts that lead us to reflect on the different attitudes that the speaker assumes before his audience. The results show that the concept of audience is multifaceted, constituted by several factors that, unified, give rise to this important argumentative instance: the enunciator. In this way, the consideration of each of the multiple faces that make up this concept, becomes paramount for its complete understanding. Still as a result, we find that the universal audience should be understood as an argumentative principle of overcoming. In addition, we highlight that the relevance of our research stems from the fact that it concentrates important reflections of classical and contemporary authors on the concept of audience, but does not stop there, since, inspired by the notions of linguistics, we went to check whether what we undertake theoretically was manifested in the current discursive practices, and we could prove this manifestation. As a result of the path we have undertaken, we can also offer to the scientific community a theoretical and analytical model that allows us to establish whether a given discourse approaches or distances itself from the maxims of universality.